Different Rates of Bioprosthetic Aortic Valve Failure With Perimount™ and Trifecta™ Bioprostheses - Lange, Rüdiger; Alalawi, Zahra; Voss, Stephanie; Boehm, Johannes; Krane, Markus; Vitanova, Keti (Frontiers in Cardiovascular Medicine, 2022)
Objectives The use of bioprostheses in surgical aortic valve replacement (SAVR) has increased in younger patients. Comparative analysis of different types of bioprostheses is lacking. We aimed to compare two proprietary bioprostheses with different designs, i.e., internally and externally mounted leaflets, focusing on the long-term durability and survival. Methods We conducted a large single-center retrospective analysis of all consecutive patients who underwent SAVR with either Perimount™ (PM) or Trifecta™ (TF) bioprostheses between 2001 and 2019. The patient groups were further subdivided by age <65 and >65. Endpoints of the study were all-cause mortality and reoperation due to bioprosthetic valve failure (BVF). Results Selection criteria resulted in a total sample of 5053 patients; 2630 received a PM prosthesis (internally mounted leaflets) and 2423 received a TF prosthesis (externally mounted leaflets). The mean age at surgery was similar (69 ± 11 y, PM, and 68 ± 10 y, TF, p=0.9), as was estimated survival at 8 years (76.1 ± 1.3%, PM, and 63.7 ± 1.9% TF; p=0.133). A total of 309 (6.1%) patients (187 PM and 122 TF) required repeat aortic valve replacement for bioprosthetic valve failure (BVF), with a median time to reoperation of 8 years [3 to 19] in the PM group and 4 years [0.6 to 8.5] in the TF group. Patients in the TF group had a significantly higher cumulative reoperation rate at 8 years compared to those in the PM group (16.9 ± 1.9% vs. 3.8 ± 0.4%; p<0.01). This difference persisted across age groups (<65 y, 13.3% TF vs. 8.6% PM; >65 y, 12% TF vs. 7% PM). Conclusion Bioprostheses for SAVR with externally mounted leaflets showed significantly higher long-term reoperation rates compared to those with internally mounted leaflets, regardless of the patient’s age at SAVR. Survival was similar with both bioprostheses.